Development of banking in India since 1949 - Pandey, Krishna Lal. (Calcutta : Scientific Book Agency, 1968)
The study is an attempt to make an impartial evaluation of the role and working of banks in India in the post-war period.
Bibliography: p. [259]-260.
osc 8/5/18
Loans
Keywords: Banks and banking; Development banks